Prenatal nicotine exposure during pregnancy results in adverse neurodevelopmental alterations and neurobehavioral deficits - Alicia C. Wells; Shahrdad Lotfipour; Shahrdad Lotfipour (Frontiers Media S.A., 2023)
Maternal tobacco use and nicotine exposure during pregnancy have been associated with adverse birth outcomes in infants and can lead to preventable pregnancy complications. Exposure to nicotine and other compounds in tobacco and electronic cigarettes (e-cigarettes) has been shown to increases the risk of miscarriage, prematurity, stillbirth, low birth weight, perinatal morbidity, and sudden infant death syndrome (SIDS). Additionally, recent data provided by clinical and pre-clinical research demonstrates that nicotine exposure during pregnancy may heighten the risk for adverse neurodevelopmental disorders such as Attention-Deficit Hyperactivity (ADHD), anxiety, and depression along with altering the infants underlying brain circuitry, response to neurotransmitters, and brain volume. In the United States, one in 14 women (7.2%) reported to have smoked cigarettes during their pregnancy with the global prevalence of smoking during pregnancy estimated to be 1.7%. Approximately 1.1% of women in the United States also reported to have used e-cigarettes during the last 3 months of pregnancy. Due to the large percentage of women utilizing nicotine products during pregnancy in the United States and globally, this review seeks to centralize pre-clinical and clinical studies focused on the neurobehavioral and neurodevelopmental complications associated with prenatal nicotine exposure (PNE) such as alterations to the hypothalamic-pituitary-adrenal (HPA) axis and brain regions such as the prefrontal cortex (PFC), ventral tegmental area (VTA), nucleus accumbens (NA), hippocampus, and caudate as well as changes to nAChR and cholinergic receptor signaling, long-term drug seeking behavior following PNE, and other related developmental disorders. Current literature analyzing the association between PNE and the risk for offspring developing schizophrenia, attention-deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD), anxiety, and obesity will also be discussed.